Iraqi Christian Monasteries and Their Educational Role During the Islamic Eras – A Historical Study Based on Islamic Geographical Literature – - Hussein, Prof. Dr. Abbas Fadhel Hussein; Alwan, Asst. Lecturer Saad Hussein Alwan (Sulaimani Journal for Humanities, 2026)
This study examines the role of Christian monasteries in Iraq during the period of Islamic rule, as documented in classical Islamic geographical sources (kutub al-buldan). It highlights their religious, social, and cultural significance throughout this historical era. These geographical texts offer rich and vivid descriptive accounts of the monasteries, portraying their rituals and religious events, which held a distinctive educational nature specific to the Christian communities of the region. In addition to their religious role, many monasteries provided public services to passing trade caravans, especially those located in desert or water-scarce areas. Naturally, offering such services fostered a rich cultural and intellectual exchange between the monasteries and their surrounding local and global environments. These monasteries served as educational centers, offering instruction to clergy, monks, and any passersby or visitors seeking knowledge. A variety of disciplines—including theology, philosophy, and medicine—were taught by senior religious figures within the monasteries.
Keywords: Monasteries; Mosul; Baghdad; Monks; AlHirah; AlDayr alAʿla; Catholicos